Soils as a key component of the critical zone. - Berthelin, J.; Valentin, Christian; Munch, Jean Charles (Environmental sciences research report. Soil set, 2018)
This introductory book to the six volume series includes an introduction defining the critical zone for mankind that extends from tree canopy and the lower atmosphere to water table and unweathered rock. Soils play a crucial role through the functions and the services that they provide to mankind. The spatial and temporal variability of soils is represented by information systems whose importance, recent evolutions and increasingly performing applications in France and in the world must be underlined. The soil functions, discussed in this book, focus on the regulation of the water cycle, biophysicochemical cycles and the habitat role of biodiversity. The main services presented are those related to the provision of agricultural, fodder and forest products, energy, as well as materials and the role of soil as infrastructure support. They also include the different cultural dimensions of soils, their representations being often linked to myths and rites, as well as their values of environmental and archaeological records. Finally, the issue is raised of an off-ground world.